PENGEMBANGAN MEDIA LUDO MATH PADA MATERI PECAHAN SEDERHANA BAGI PESERTA DIDIK KELAS III SEKOLAH DASAR - Alfiatun Nur Azizah; Meita Fitrianawati (WASIS : Jurnal Ilmiah Pendidikan, 2020)
This research aims to determine the steps of media development and to know the quality and feasibility of Ludo Math media.The Ludo Math media was developed with a Borg and Gall model consisting of; 1) research and information collecting, 2) planning, 3) develop preliminary form of product, 4) preliminary field testing, 5) main product revision, 6) main field testing, 7) operational product revision, and 8) operational field testing.  The study was conducted at SD NegeriGetas 02 with the subject students training class III.  Data collection techniques in the form of observation, interviews, assessment sheets of experts and teachers, and student response sheets.Analysis of the data of this study includes qualitative data analysis and quantitative data analysis.  The results of this study indicate that the assessment according to media experts obtained a value of 85 with the category "Very Good". Assessment according to learning experts obtained a value of 92.5 with the category "Very Good".  The assessment according to the material experts obtained a value of 87.5 with the category "Very Good".  Small Group Product Trial Results, teacher assessment and student responses obtained an average value of 96.25 with the category "Very Good".  The results of the Large Group Usage Trial, the assessment of teachers and students obtained an average value of 98.75 in the "Very Good" category. From all assessments of experts, teachers, and students, Ludo Math media get an average value of 92. If the average value is converted into qualitative data, Ludo Math media is included in the "Very Good" category and declared fit for use in the material Simple fractions class III elementary school.